Analysis of Patient Bed Product Quality Control with Six Sigma Method and Failure Mode and Effects Analysis (FMEA) (Case Study of PT. Karya Indah Medika) - Okstevia, Almiranda Shafira; Sumiati, Sumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT. Karya Indah Medika is a manufacturing company engaged in the production of hospital furniture. One such product is a patient bed. In each period of patient bed production, there are still defects that occur such as coating defects, dented iron, and broken wheels. The purpose of this study is to determine the percentage of defects, and the causes of defects, and to obtain the greatest risk of failure in the production process in the RPN value so that the type of failure can be determined which should be prioritized first so as soon as possible corrected and determined corrective steps to reduce product defects. The research method used is Six Sigma and Failure Mode Effect Analysis (FMEA). The Six Sigma method includes Define, Measure, Analyze and Improve which will be used to determine the percentage of defects that occur. While the FMEA method is carried out as an effort to improve quality. Based on the research calculations, the results obtained were a sigma value of 3.19σ. Based on calculations using the FMEA method, the largest RPN is obtained for coating defects, namely ink absorption that is not optimal, broken wheel defects, namely operators who are too hasty during assembly, and dented iron defects, inappropriate material quality. Advice that can be given is to control and monitor ink absorption, operators who are more careful and not in a hurry, and check the quality of raw materials before processing.